EFL Teachers' Perceptions and Experiences Using Quizizz for Grammar Assessment: Benefits, Challenges, and Impact on Student Engagement and Learning Outcomes - Sonya Veningsih Cheryanti Benu (Indonesian Journal of Foreign Language Studies, 2026)
This study explored EFL teachers' perceptions and experiences using Quizizz for grammar assessment, focusing on its benefits, challenges, and impact on student engagement and learning outcomes. This research employed descriptive qualitative as the design. This research conducted a semi-structured interview with four EFL teachers, who use Quizizz for grammar assessment. The findings reveal that Quizizz significantly enhances student engagement due to its interactive and gamified features, which make grammar exercises more enjoyable and stimulating. Immediate feedback and the ability to customize quizzes were highlighted as major benefits, contributing to improved student motivation and better learning outcomes. The participants also reported several challenges in implementing Quizizz. Technical issues such as internet connectivity problems and limited device availability were common obstacles. Additionally, the time required to create customized quizzes and aligned them with the curriculum posed significant challenges. Teachers also expressed concerns about their own digital literacy and the need for professional development to effectively utilize the platform. The research underscored the potential of digital tools like Quizizz to transform traditional grammar assessment methods, provided that adequate support and resources were made available to teachers.